SYSTEM AND METHOD FOR PARTIALLY UPDATING MAP DATA BASED ON USER'S MOVEMENT PATH, SERVICE APPARATUS AND TERMINAL APPARATUS THEREOF, AND RECORDING MEDIUM THEREFOR (2012)
The present invention relates to a system and a method for partially updating map data based on a user's movement path, a service apparatus and a terminal apparatus thereof, and a recording medium therefor, and the method includes checking a major movement path of a user; receiving map data update information; extracting partial map data to be updated from map data matched with the major movement path of the user to request update information for the extracted partial map data; and receiving the requested update information on the partial map data to update the map data, and according to the present invention, map data matched with a user's major movement path is partially updated by determining the user's major movement path to more efficiently update the map data.